Beyond people group thinking: A critical reevaluation of unreached people groups. Issue 3 (July 2018) - Lee, Peter T.; Park, James Sung-Hwan
Since its inception at the 1974 Lausanne Congress, the concept of "unreached people groups" (UPG) has revolutionized global mission. Today, "people group thinking" represents perhaps the predominant paradigm in global mission. Yet for all its influence, few have carefully examined UPG's questionable underlying assumptions. This article critically reevaluates two central tenets of UPG. First, using biblical and sociocultural analysis, we assess the conceptual foundation of UPG—the idea of the people group. Second, we engage theologically with mission strategies that arise from UPG. We conclude that UPG relies upon flawed biblical, theological, and sociocultural assumptions, and propose that missiology move beyond UPG in theory and practice.